Phytochemical Investigation of the Aerial Part of Iraqi Convolvulus arvensis - Alwan, Mustafa H.; N. Hamad, Maha (Iraqi Journal of Pharmaceutical Sciences, 2020)
Convolvulus arvensis is a species of bindweed that is rhizomatous and is in the morning glory family (Convolvulaceae) native to Europe and Asia. The plant is naturally grown in Iraq. The plant was reported to be used in traditional medicine from as early as 1730s. The Aerial parts of Convolvulus arvensis were macerated in 80% ethanol for 6 days. The concentrated extract was partitioned with n-hexane, chloroform, ethyl acetate- and n-butanol successively. The n-hexane and ethyl acetate, fractions were examined for the presence of phytochemicals by thin layer chromatography and high performance liquid chromatography and its steroid and flavonoid contents were investigated. Stigmasterol was isolated from n-hexane fraction and identified by liquid chromatography/mass spectroscopy. Rutin was isolated from the ethyl acetate fraction and identified by liquid chromatography/mass spectroscopy. The aim is to examine the phytochemical constituents of the aerial parts of Convolvulus arvensis, literature survey available so far revealed that there were no studies about the phytochemical investigation for Convolvulus arvensis in Iraq. Different chromatographic techniques like Thin Layer Chromatography and mass spectroscopy were used and the presence of Stigmasterol and Rutin in aerial parts of Convolvulus arvensis was indicated.